KUALITAS SUMBER DAYA MANUSIA, PROFESIONALISME KERJA, DAN KOMITMEN SEBAGAI FAKTOR PENDUKUNG PENINGKATAN KINERJA KARYAWAN PDAM KABUPATEN BATURAJA - Erfin Mardalena (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This study aims to determine the effect of human resource quality, professionalism of work, commitment to employee performance PDAM Baturaja partially and simultaneously. Research approach used in this study is quantitative. Population in the company amounted to 150 and taken 75 respondents to use the sample with the sampling method is simple random sampling or simple random sample by means of a lottery / raffle of names of employees PDAM Baturaja is then taken as samples used lottery of 75 names of employees Selected in the draw. Methods of analysis using multiple linear regression analysis were used to determine the influence of strong between the dependent variable and independent variables. The test results and analysis conducted states that the variable quality of human resources and a significant positive effect on employee performance PDAM Baturaja Regency. Variable professionalism and significant positive effect on employee performance PDAM Baturaja. And variable commitment and significant positive effect on employee performance PDAM Baturaja. And the quality of human resources, professionalism, and commitment to simultaneously positive and significant influence on employee performance PDAM Baturaja Regency.